2008
DOI: 10.1016/j.biocel.2007.10.032
|View full text |Cite
|
Sign up to set email alerts
|

The SarA protein family of Staphylococcus aureus

Abstract: Staphylococcus aureus is widely appreciated as an opportunistic pathogen, primarily in hospitalrelated infections. However, recent reports indicate that S. aureus infections can now occur in other wise healthy individuals in the community setting. The success of this organism can be attributed to the large array of regulatory proteins, including the SarA protein family, used to respond to changing microenvironments. Sequence alignment and structural data reveal that the SarA protein family can be divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 22 publications
(46 reference statements)
7
172
0
2
Order By: Relevance
“…S. aureus, a major human pathogen that is the most common source of bacterial infections in the community and hospital, causes a wide variety of diseases, ranging from minor skin infections to life-threatening blood infections (28). The virulence of this organism is controlled by regulatory networks composed of a large array of regulatory proteins, such as the agr system and the staphylococcal accessary protein A (SarA)/ MarR family global transcriptional regulator A (MgrA) family global regulatory proteins, which can respond to changing host microenvironments (29,30). Recent studies have revealed that the sole and conserved Cys residue in SarA, MgrA, and SarZ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus, a major human pathogen that is the most common source of bacterial infections in the community and hospital, causes a wide variety of diseases, ranging from minor skin infections to life-threatening blood infections (28). The virulence of this organism is controlled by regulatory networks composed of a large array of regulatory proteins, such as the agr system and the staphylococcal accessary protein A (SarA)/ MarR family global transcriptional regulator A (MgrA) family global regulatory proteins, which can respond to changing host microenvironments (29,30). Recent studies have revealed that the sole and conserved Cys residue in SarA, MgrA, and SarZ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While there is no question that SarA is required for virulence determinant regulation, the mechanism by which SarA manifests its regulatory effects remains to be settled (36,64,138,186,217). Compounding the difficulty in defining SarA's mechanism of action is the fact that SarA represents one member of the SarA family of proteins, which consists of at least 11 members (34).…”
Section: Overview Of Staphylococcal Virulence Factor Regulationmentioning
confidence: 99%
“…The success of this bacterium in pathogenesis is largely owing to the sophisticated regulatory network composed of several global transcriptional regulators (e.g., SigB, Rot, MgrA, SarA, and SarA homologs) and 16 two-component systems (TCSs) (e.g., agr, srrAB, arlRS, vraRS, hssRS, and saeRS) (10)(11)(12), which enable the bacterium to rapidly sense and adapt to changing environment. Central to this regulatory network is the quorum-sensing agr system, which controls the expression of bacterial virulence in response to changes in cell density (10).…”
mentioning
confidence: 99%